APPROACHES TO JUSTIFICATION OF AGRICULTURAL LAND RECLAMATION IN THE SOUTH OF UZBEKISTAN UNDER POSSIBLE CHANGES IN CLIMATIC INDICATORS - B. M. Kholbaev (Web of Journals Publishing, 2024)
The development and location of agricultural land reclamation is directly related to climatic changes. Today, the problem of adaptation of agricultural production, as the most sensitive and vulnerable to climatic factors, comes to the forefront.